Soft computing in management and business economics : Volume 1 - Gil-Lafuente, Jaime; Merigó-Lindahl, José M.; Gil-Lafuente, Anna M. (Studies in Fuzziness and Soft Computing, 2012)
This book is a collection of selected papers presented at the Annual Meeting of the European Academy of Management and Business Economics (AEDEM), held at the Faculty of Economics and Business of the University of Barcelona, 05 - 07 June, 2012. This edition of the conference has been presented with the slogan "Creating new opportunities in an uncertain environment". There are different ways for assessing uncertainty in management but this book mainly focused on soft computing theories and their role in assessing uncertainty in a complex world. The present book gives a comprehensive overview of general management topics and discusses some of the most recent developments in all the areas of business and management including management, marketing, business statistics, innovation and technology, finance, sports and tourism. This book might be of great interest for anyone working in the area of management and business economics and might be especially useful for scientists and graduate students doing research in these fields.